2019
DOI: 10.33474/jpm.v5i1.2627
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Penalaran Matematis Peserta Didik Melalui Model Pembelajaran Reciprocal Teaching Dengan Berbantuan Alat Peraga “Kartu Pintar” Pada Materi Prisma Dan Limas Kelas VIII SMP Negeri 1 Pandaan Tahun Ajaran 2017/2018

Abstract: The purpose of this study was to determine whether there is an increase in mathematical reasoning abilities and to describe the mathematical reasoning abilities of students through the Reciprocal Teaching learning model assisted with "smart card" teaching aids on prism and pyramid material class VIII Public Middle School 1 Pandaan 2017/2018 Academic Year. The research method used in this study, which is a mixed method with an experimental mixed method design design, was to wrap a basic mixed method design into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
0
0
4
Order By: Relevance
“…Indonesian students have difficulty solving PISA problems because of its problems are very demanding of reasoning and problem-solving ability while they usually solve a mathematics problem that emphasizes mastery of basic mathematics skills. This is in line with the results of Oktaviana et al (2018), Damayanti and Yunianta (2018), and Aprianti and Kesumawati (2019) study which reported that students' mathematical problem-solving ability is not optimal yet, likewise their mathematical reasoning ability according to Handini et al (2015), Napitupulu et al (2016), and Cahyani (2019) study. The abilities are not optimal, according to Afgani (2018) showed that the students' mathematical understanding scheme has a problem.…”
Section: Introductionsupporting
confidence: 87%
“…Indonesian students have difficulty solving PISA problems because of its problems are very demanding of reasoning and problem-solving ability while they usually solve a mathematics problem that emphasizes mastery of basic mathematics skills. This is in line with the results of Oktaviana et al (2018), Damayanti and Yunianta (2018), and Aprianti and Kesumawati (2019) study which reported that students' mathematical problem-solving ability is not optimal yet, likewise their mathematical reasoning ability according to Handini et al (2015), Napitupulu et al (2016), and Cahyani (2019) study. The abilities are not optimal, according to Afgani (2018) showed that the students' mathematical understanding scheme has a problem.…”
Section: Introductionsupporting
confidence: 87%
“…Ada beberapa indikator penalaran matematika yang perlu dimiliki peserta didik yaitu membuktikan kebenaran suatu argumen dan juga untuk membuat arguman baru yang valid serta melakukan inferensi dalam kecerdasan buatan (artificial intellegence) [8]. Indikator penalaran untuk melakukan pemecahan suatu permasalahan matematika, yakni: "mengajukan dugaan; melaksanakan manipulasi matematika; melakukan penarikan kesimpulan; melakukan pengumpulan bukti serta argumen ataupun bukti untuk mendukung klaim bahwasanya jawaban yang diberikan adalah akurat; menemukan pola ataupun kualitas fenomena matematika diperlukan untuk membuat generalisasi" [9]. Adapun indikator penalaran yang digunakan pada penulis, yakni: memberikan alasan terhadap suatu argumen; membuat kesimpulan sesuai pernyataan; membuat generalisasi dan melakukan manipulasi matematika.…”
Section: Pendahuluanunclassified
“…Berdasarkan tujuan dalam pembelajaran matematika, aspek dalam pengembangan kemampuan penalaran matematis siswa sudah memperhatikan kurikulum yang sudah tersusun. Namun, pada kondisi saat ini kemampuan penalaran matematis siswa dalam pembelajaran matematika di sekolah dianggap kurang dan tidak menekankan secara khusus (Cahyani, 2019). Hal tersebut dapat terlihat melalui laporan dari survei yang dilakukan oleh TIMSS dan PISA yang memperlihatkan kurangnya rata-rata nilai matematis siswa di Indonesia.…”
Section: Pendahuluanunclassified
“…Alat peraga merupakan alat yang dipergunakan dalam menjelaskan konsep dalam matematika (Cahyani, 2019). Alat peraga tersebut merupakan alat bantu yang dapat digunakan guna melancarkan proses pembelajaran matematika.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation